Primate comparative neuroscience using magnetic resonance imaging: promises and challenges - Mars, Rogier B.; Neubert, Franz-Xaver; Verhagen, Lennart; Sallet, Jérôme; Miller, Karla L.; Dunbar, Robin I. M.; Barton, Robert A. (Frontiers in Neuroscience, 2014)
Primate comparative anatomy is an established field that has made rich and substantial contributions to neuroscience. However, the labor-intensive techniques employed mean that most comparisons are often based on a small number of species, which limits the conclusions that can be drawn. In this review we explore how new developments in magnetic resonance imaging have the potential to apply comparative neuroscience to a much wider range of species, allowing it to realize an even greater potential. We discuss (1) new advances in the type of data that can be acquired, (2) novel methods for extracting meaningful measures from such data that can be compared between species, and (3) methods to analyse these measures within a phylogenetic framework. Taken together, these developments will allow researchers to characterize the relationship between different brains, the ecological niche they occupy, and the behavior they produce in more detail than ever before.